Enhancement of Aluminum-Air Battery Performance Using Rice Husk-Derived Carbon Quantum Dots and Carbon Nanotubes - Zakky, Muhammad Ammar; Ridwan, Firman; Agusto, Dean Bilalwa; Wismalqi, Wismalqi; Gusriwandi, Gusriwandi (Green Engineering Society, 2025)
The development of sustainable, high-performance energy storage systems is crucial for addressing the challenges associated with renewable energy integration and the limitations of conventional lithium-ion batteries. This study investigated the potential of an innovative electrolyte membrane for aluminum-air batteries, incorporating carbon quantum dots (CQDs) derived from rice husk charcoal and carbon nanotubes (CNTs) within a polyvinyl alcohol (PVA) matrix. CQDs were synthesized using a microwave-assisted technique, and CNTs were added to enhance the structural and conductive properties of the membranes. Three distinct membrane compositions were prepared: a base solution of PVA, HCl, and glycerol; a base solution with CQDs; and a base solution with CQDs and CNTs. Fourier Transform-Infrared (FT-IR) spectroscopy revealed enhanced intermolecular interactions and successful integration of the carbon nanomaterials within the polymer network. X-ray diffraction (XRD) analysis indicated a reduction in crystallite size from 11.27 nm (base membrane) to 9.65 nm (–14.36%) with CQDs and further to 8.29 nm (–26.47%) with CQDs + CNTs, suggesting improved amorphous characteristics that reinforce the membrane structure and facilitate ionic conductivity. Electrochemical impedance spectroscopy (EIS) demonstrated an increase in ionic conductivity from 4.98501 mS/cm (base membrane) to 5.51837 mS/cm with CQDs and 6.35292 mS/cm (+27.4%) with CQDs + CNTs. These findings highlight the synergistic effect of CQDs and CNTs in optimizing the ion migration pathways and charge transport within the electrolyte membrane. The utilization of rice husk charcoal as a precursor for CQDs aligns with sustainable practices and promotes the use of renewable resources. This study presents a promising approach for the development of advanced electrolyte membranes for aluminum-air batteries, contributing to efficient, environmentally friendly, and cost-effective energy storage solutions.